Semantic representation and interval roughness analysis of IoT CapBAC rules - Xiaoyan LIANG; Ruizhong DU (Tongxin xuebao)
To break the bottleneck of interval roughness analysis, a rule semantic model IoTACS was proposed, and IoTRA algorithm was given.In IoTACS, a conceptual structure of the IoT CapBAC rule domain was proposed, the quantitative data properties of the basic concepts were given, then the semantic tree model of rule semantics was proposed, the time relations of the time ontology were extended and its quantitative logical representation was given.As the theoretical basis, it was proved that the root cause of interval inconsistency was roughness, and its logical formalization of the roughness was given.The case study shows that IoTRA can help to improve the accuracy of the authorized interval, and the IoTACS model have higher readability than the formal model.The comparison experiments with the IoTC2 algorithm on the inconsistency analysis show that the response time of the IoTRA algorithm is more significantly reduced.